2011
DOI: 10.3389/fendo.2011.00036
|View full text |Cite
|
Sign up to set email alerts
|

A Gonadotropin-Releasing Hormone-Like Molecule Modulates the Activity of Diverse Central Neurons in a Gastropod Mollusk, Aplysia Californica

Abstract: In vertebrates, gonadotropin-releasing hormone (GnRH) is a crucial decapeptide that activates the hypothalamic–pituitary–gonadal axis to ensure successful reproduction. Recently, a GnRH-like molecule has been isolated from a gastropod mollusk, Aplysia californica. This GnRH (ap-GnRH) is deduced to be an undecapeptide, and its function remains to be explored. Our previous study demonstrated that ap-GnRH did not stimulate a range of reproductive parameters. Instead, it affected acute behavioral and locomotive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Orthologs of vertebrate GnRH have recently been discovered in protostomes, but their physiological roles are not clearly defined [ 3 5 ]. Physiological studies using native GnRH in molluscan models suggest protostome forms of GnRH have become highly diversified and are multi-functional molecules responsible for a wide range of regulation including neural control [ 6 ], motor activity [ 6 , 7 ], feeding [ 7 ], and reproduction [ 8 10 ]. Further, the presence of additional molecules that are orthologous to protostome GnRH, including adipokinetic hormone (AKH), corazonin (CRZ), and AKH/CRZ-related peptide (ACP), have been documented [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orthologs of vertebrate GnRH have recently been discovered in protostomes, but their physiological roles are not clearly defined [ 3 5 ]. Physiological studies using native GnRH in molluscan models suggest protostome forms of GnRH have become highly diversified and are multi-functional molecules responsible for a wide range of regulation including neural control [ 6 ], motor activity [ 6 , 7 ], feeding [ 7 ], and reproduction [ 8 10 ]. Further, the presence of additional molecules that are orthologous to protostome GnRH, including adipokinetic hormone (AKH), corazonin (CRZ), and AKH/CRZ-related peptide (ACP), have been documented [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These finding can be confirmed in the future with physiological studies using purified or synthetic ly-GnRH/CRZ peptide. Our results further suggest the term "invGnRH" (e.g., oct-GnRH, ap-GnRH) should be revised to avoid the connotation that these peptides serve specialized reproductive function similar to vertebrate GnRHs (Iwakoshi et al, 2004;Minakata et al, 2009;Tsai et al, 2010;Sun and Tsai, 2011;Treen et al, 2012;Jung et al, 2014. Nagasawa et al, 2015Kavanaugh and Tsai, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…In other words, invGnRH/CRZ molecules, initially named invGnRH (e.g., oct-GnRH, ap-GnRH), may not assume a specialized reproductive role as seen in vertebrate GnRH. Indeed, emerging evidence suggests diverse biological effects of invGnRH/CRZ that include not only reproductive, but also motor, behavioral, and neuromodulatory functions (Iwakoshi et al, 2004;Minakata et al, 2009;Tsai et al, 2010;Sun and Tsai, 2011;Treen et al, 2012;Jung et al, 2014. Nagasawa et al, 2015 Kavanaugh and Tsai, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…19 In Aplysia, it has been demonstrated that peptides released by the bag cells during and after discharge have a number of effects on the electrical activity of central neurons in vitro. 20 These peptides also affect gill and siphon contractions and the arterial system. Injections of these peptides into intact animals also induce behavioral changes.…”
Section: Role Of Caudo Dorsal Cells (Cdcs)mentioning
confidence: 99%